Eating and Drinking at the Royal Hospital of Mozambique Island: Medicine and Diet Change between the end of the 18th and the early 19th century - Eugénia Rodrigues (Afriques)
This article analyses the social construction of the hospital diet in Mozambique Island and the process of dietary change induced by the European medical discourse and extended to the East African colonial world, at the end of the Ancien Régime. Mozambique Island, former capital of the Portuguese East Africa colony, was the crossing point of people from various continents, where culinary traditions sometimes mingled together and sometimes coexisted side by side. These foodways were incorporated into the Royal Hospital diet, which combined dishes of Indian, Portuguese, and African origin. Between the late 18th and the early 19th century, the intervention of the European chief-physicians in the hospital diets tended to configure the patients’ food in accordance with the changes taking place in European medical discourse and to exclude certain dishes which had a strong local tradition.